20 Development of a digital guide for families of patients on the GOSH paediatric intensive care unit. (30th November 2020) - Du, Yu; Fang, Yuexi; Sakelyte, Kamile; Bassi, Daiana; Conner, Sue; Fu, Yun; Mohamedally, Dean; Molyneux, Gemma; Roberts, Graham; Sebire, Neil J; Ndokera, Rufaro; Ray, Samiran
Abstract : Paediatric Intensive Care Units (PICUs) can be very stressful environments for families of sick children. PICU has more restrictions than general wards, and activities such as visiting hours can be very different from other areas of the hospital. Currently, information is available to families in paper form and displayed around the unit. However, we would like to revolutionise our communication strategy to make information available digitally in the form of a mobile app, allowing families to engage with this information more flexibly. As part of a joint collaboration between GOSH and UCL computer science (CS) through the industry exchange network, a mobile app that delivers information to parents was developed using Ionic. A web application, which allows clinical teams to manage content, was developed using NodeJS with a MySQL database. The mobile app delivers a broad range of information about the PICU ward, including information on access, staff groups, and equipment used. In addition, a FAQ section is included that was developed in partnership with patients and families. The submission of Feedback is also possible via the app; this allows users to submit questions, or comments, on the content and information. This mobile app is an example of how the Hospital might develop new ways of communicating important information to patients and families using our services.